2008
DOI: 10.1016/j.joen.2008.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Phosphophoryn Promotes Cellular Migration of Human Dental Pulp Cells

Abstract: Dentin phosphophoryn (DPP) is a dentin sialophosphoprotein gene product that has an RGD motif and repeat sequences of aspartic acid and phosphoserine. To date, the function of DPP in the early stage of reparative dentin formation still remains unclear. The objective of this study was to evaluate the effects of DPP on pulp cell migration and proliferation. DPP promoted cell migration in a concentration-dependent manner, thus increasing it by about 3-fold at 1000 ng/mL compared with the control, but it had no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…It is reported that dentin phosphophoryn promoted differentiation and cell migration by acting on integrins on the surface of DPCs via RGD motif (32). Furthermore, both osteogenic markers DMP-1 and OPN share the same integrin receptorbinding site during cell attachment in vitro, whereas integrins aVb3 or aVb5 can promote cell attachment to BSP, suggesting there might be an interaction between osteogenic markers and integrins acting on cell adhesion and migration (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that dentin phosphophoryn promoted differentiation and cell migration by acting on integrins on the surface of DPCs via RGD motif (32). Furthermore, both osteogenic markers DMP-1 and OPN share the same integrin receptorbinding site during cell attachment in vitro, whereas integrins aVb3 or aVb5 can promote cell attachment to BSP, suggesting there might be an interaction between osteogenic markers and integrins acting on cell adhesion and migration (33).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using LL37 as a pulp-capping agent on reversibly inflamed pulp may be effective for pulp healing and the formation of reparative dentin. Dentin phosphophoryn also promotes HP cell migration (31). Its traditional role is to induce dentin calcification (32).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DPP activates Smad-1 via integrin signaling independently of BMP signaling (52). Also, an RGD peptide derived from porcine DPP promotes cellular migration of human dental pulp cells (53). Taken together, these observations indicate that DSPP functions as a cell-signaling molecule.…”
Section: The Functional Analysis Of Dspp Dmp-1 By Gene Knockout Amentioning
confidence: 99%